Acute Stress Attenuates Cognitive Flexibility in Males Only: An fNIRS Examination - Kalia, Vrinda; Vishwanath, Karthik; Knauft, Katherine; Vellen, Bryan Von Der; Luebbe, Aaron; Williams, Amber (Frontiers in Psychology, 2018)
The ability to control one’s thoughts to achieve goal-directed behavior is known as cognitive control. Empirical evidence in the past few years has demonstrated that cognitive processes underlying cognitive control can be influenced by acute stress. The impact of acute stress on cognitive flexibility, a key aspect of cognitive control, has received little attention in the literature. We present the result of two experiments conducted to examine the effect of acute stress on cognitive flexibility. Acute stress was induced using the cold pressor task (CPT). Cognitive flexibility was assessed using the Wisconsin Card Sorting Test (WCST). Across both experiments acute stress had an attenuating effect on task switching, on the WCST. Our findings also indicate that this effect was moderated by the participant’s gender. In Study 1 we observed that following stress exposure male participants in the stress condition made more perseverative errors than participants in the control group. In Study 2 we examined the bilateral hemodynamics in the pre-frontal cortex (PFC) during acute stress induction using functional near infrared spectroscopy (fNIRS). Our analysis indicated that magnitude of changes in the functional oxyHb signals were larger than those in the systemic components for participants in the stress group relative to control. In addition, oxyHb levels post stress induction were correlated with performance on the WCST for the male participants in the stress group only. Concordant with previous reports, our findings indicate that acute stress impacts cognitive flexibility in males and females differentially. Our work also demonstrates the feasibility of using fNIRS as a practical and objective technique for the examination of hemodynamics in the PFC during acute stress.